Sensitivity analysis of Typhoid Fever model with Saturated Incidence rate. - Kehinde Bashiru; Mutairu Kolawole; Taiwo Ojurongbe; Mutiu Olaosebikan; Nureni Adeboye; Habeeb Afolabi (Mathematics and Computational Sciences, 2024)
In this study, a dynamic model for typhoid fever incorporating protection against infection in the presence of saturated incidence rate is proposed. The existence and uniqueness solution is proved in order to ascertain the existence of the model. Stability analysis of endemic and disease free equilibrium was carried out to investigate the dynamic behavior of the transmission of the disease in a given population. Sensitivity analysis was also carried out to detect the impact of the parameters of the reproductive number and which parameters should focus as a control intervention. Numerical simulation of the model was carried out and the result is presented graphically, the result shows that an increase in the probability of the sources of protection and sociology factor dictate low disease prevalence in a population.